Pelestarian Lingkungan Laut Melalui Pengelolaan Wilayah Pesisir Berbasis Masyarakat Oleh Pemerintah Desa/Kelurahan - Zunnuraeni Zunnuraeni (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2018)
Coast And small islands have a different kind of natural resources, that have important role for the social, economic, and environment development and also for national sovereignty optimally. For management of coast may getting optimally it must undertake by involved society. Coast Management Based on Society need responsibility and capability of society therefore they can involved actively.